Faktor Penyebab Remaja Putus Sekolah Di Jorong Setia Kecamatan Dua Koto Kabupaten Pasaman - Yogi Pratama; Salmi Wati; Arifmiboy Arifmiboy; Iswantir M (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This research is motivated by the existence of an initial phenomenon in Jorong Setia Kec. Two Koto Kab. In Pasaman, there are still teenagers who drop out of school at school age. Temporary assumptions are caused by internal and external factors that prevent children from acquiring knowledge. Based on the problems stated above, the purpose of this research is to find out the factors that cause adolescents dropping out of school in Jorong Setia Kec. Two Koto Kab. Passover. So the authors are interested in doing this research. Research on the Causes of Teenagers Dropping Out of School in Jorong Setia, Dua Koto District, Pasaman Regency, the type of research that the author uses is field research, namely collecting data directly from research locations to support the success of a case using relevant methods. The method used by the authors in this study is a qualitative descriptive method by describing the factors of youth dropping out of school in the view of Islamic education, as key informants are adolescents who have dropped out of school in Jorong Setia, Dua Koto District. Data collection techniques that the authors use are interviews and documentation. The results of research in Jorong Setia Kec. Two Koto Kab. Pasaman is the cause of teenagers dropping out of school from internal factors and external factors, first: from internal factors, namely children just want to play compared to school. Second: school is considered unattractive because of the tasks and rules at school that they cannot follow. Third: the inability to follow lessons because the child feels that the lessons given by the teacher at school are very difficult for him and the child also does not like the way the teacher explains the lesson. Fourth: from external factors, namely the low economic status of parents so that they cannot afford to send their children to school. Fifth: lack of parental attention, namely parents are too busy with work and pay less attention to and control their children. Keenan: the playing environment, namely most children are not good at adjusting to their friends, causing children to be affected by negative things.